The effect of rainfall distribution to production of oil palm in different location / Muhammad Shafiq Kota - Kota, Muhammad Shafiq (Faculty of Plantation and Agrotechnology, 2017)
Oil palm is one of important crop in Malaysia. Recently, the production of oil palm was decreased due to many factor including the climate. The rainfall distribution will effected the growth and development of palm trees which turn effect the production of the oil palm. The lacked of rainfall distribution effect the development of flower in the palm trees and increases of abortion, failed or rotten bunch, low productivity and long inflorescences about 8-9 month. The shortage of water in oil palm can cause the nutrient deficiency in oil palm trees. Whereas excessive rainfall lead to high erosion and landslide potential, which in areas that close to the river there is a potential of flooding. The excess rainfall also damages the fresh fruit bunch (EFB), reduces road quality, inhibit harvest activity, and flooding (Arif, 2015). This study was conducted to investigate the effect the rainfall distribution to the production of oil palm and to identify suitable precipitation to the maximum production of oil palm. Data of rainfall distribution and production for 2 years, 2014 and 2015 was collected from 2 estate. The result showed that in Kulim estate in 2014, P-value>0.05 there no significant different between rainfall and the production. That means the relationship between was weak positive relation between rainfall distribution and production but in 2015 result show P-value<0.05 there have significant different between rainfall and the production. While in Tabung Haji Estate the result show P-value>0.05 there are no significant different between rainfall and the production of oil palm for the both years. So, its show rainfall are not strong factors effect directly to the production of oil palm. The high amount of rainfall caused the flooding and effect the morality of the palm oil trees. The suitable rainfall are 1800 mm until 2000 mm and average 166.67 mm per monthly, if below than 700 mm the oil palm trees was died. The rainfall is not 100% affected the production but the management and the awareness of stakeholders or government agencies must be consider and make something adaption to prevent the excess or deficit of amount rainfall and the improvement of the variety tolerant of the extreme condition.